AXILLARY LYMPH NODE DISSECTION IN THE MANAGEMENT OF BREAST CANCER - Serdar Özbaş; Savaş Koçak (European Journal of Breast Health, 2006)

(untitled)
Axillary lymph node dissection (ALND) has traditionally been considered as a standard procedure in the surgical management of patients with breast cancer. The advantages of ALND in breast cancer surgery are to stage the disease, to provide accurate prognostic information, to maintain local control in the axilla and to provide a rational decision-making about adjuvant systemic therapy. Although controversial, ALND may also be associated with a small survival benefit. Recently, the question of whether ALND is needed for every patient with invasive breast cancer has been the subject of ongoing debate in the literature. The changes in the presentation and management of breast cancer (i.e., increased detection of very small breast cancers during mammographic screening, use of adjuvant systemic therapy for women with both node-positive and node-negative breast cancer, and a greater recognition of the morbidity of ALND) have prompted a re-evaluation of the need for routine ALND. More conservative techniques such as sentinel lymph node biopsy can also accurately predict nodal status with minimal morbidity, and reserves ALND for patients with positive sentinel lymph node biopsies.